Jasmonic acid and nitric oxide protects naranjilla (Solanum quitoense) against infection by Fusarium oxysporum f. sp. quitoense by eliciting plant defense responses. (April 2019) - Ávila, Ana Cristina; Ochoa, José; Proaño, Karina; Martínez, M. Carmen
Abstract: Naranjilla ( Solanum quitoense ) is an Andean tropical fruit of the solanaceae family with high nutritional value. Its cultivation is gravely affected by the lethal disease produced by Fusarium oxysporum f.sp. quitoense, causing severe economic losses. In this work we studied the possibility of boosting the plants' natural defenses to the fungus by using plant hormones. Our results show that spraying jasmonic acid or sodium nitroprusside (a NO donor) on naranjilla plantlets before Fusarium inoculation protected them from infection, and elicited strong activation of the corresponding signaling pathway, suggesting a mechanism of defense priming triggered by those compounds. Graphical abstract: Naranjilla ( Solanum quitoense ) is a crop of the Amazon basin, the cultivation of which is threatened by Fusarium oxysporum . Priming natural defences is a promising strategy with low environmental costs. Image 1 Highlights: Activation of S. quitoense defenses against F. oxysporum requires induction of the jasmonic acid pathway. Natural defenses of S. quitoense against F. oxysporum can be primed by pre-treatments with either jasmonic acid or NO. Priming natural defenses in plants is an excellent strategy to fight diseases, with low environmental costs.